Comparison of FibroScan-Aspartate Aminotransferase (FAST) Score and Other Non-invasive Surrogates in Predicting High-Risk Non-alcoholic Steatohepatitis Criteria - Lee, Jae Seung; Lee, Hye Won; Kim, Beom Kyung; Park, Jun Yong; Kim, Do Young; Ahn, Sang Hoon; Jang, Jae Young; Park, Soo Young; Lee, Hyun Woong; Lee, Chun Kyon; Kim, Seung Up (Frontiers in Medicine, 2022)
Identification of nonalcoholic steatohepatitis (NASH) with high activity and fibrosis is a major priority in patients with nonalcoholic fatty liver disease. We validated the predictive value of the FibroScan-aspartate aminotransferase (FAST) score and other noninvasive fibrosis surrogates in predicting high-risk NASH criteria. This multicenter retrospective study recruited 251 biopsy-proven nonalcoholic fatty liver disease (NAFLD) patients (132 [52.6%] men) between 2011 and 2014. The FAST score was calculated using transient elastography data and aspartate aminotransferase (AST) levels. The NAFLD fibrosis score (NFS), fibrosis-4 index (FIB-4), and AST to platelet ratio index (APRI) were calculated using biochemical data. The area under the receiver operating characteristic curves (AUCs) of the FAST score, liver stiffness, NFS, FIB-4, and APRI were 0.752, 0.718, 0.609, 0.650, and 0.722 for NAFLD activity score (NAS) ≥5 (n=117, 46.6%); 0.788, 0.754, 0.649, 0.701, and 0.747 for fatty liver inhibition of progression-NASH with histologic activity ≥3 (n=202, 80.5%); 0.807, 0.806, 0.691, 0.732, and 0.760 for severe disease with activity ≥3 and/or fibrosis ≥3 (n=132, 52.6%); and 0.714, 0.812, 0.748, 0.738, and 0.669 for NASH with NAS ≥4 and fibrosis ≥2 (n=70, 27.9%), respectively. The FAST score had the highest AUC for the most high-risk NASH criteria, except for in predicting NAS ≥4 and fibrosis ≥2. The liver stiffness value showed consistently acceptable performance in predicting all high-risk NASH criteria. The FAST score has acceptable performance in identifying high-risk NASH. However, liver stiffness alone was not inferior to the FAST score.